Implications of bioturbation induced by Procambarus clarkii on seepage processes in channel levees - Bendoni, Michele; Mazza, Giuseppe; Savoia, Nicola; Solari, Luca; Tricarico, Elena (International journal of sediment research, 2024)
River levees are subject to bioturbation by various animals which can actively excavate into earthen structures producing an internal erosion that, during the passage of a flood, can grow in time making the levee unstable. This phenomenon can lead to river levee breaching and, as a consequence, collapse, even for relatively minor flood events. A well-known animal burrower is represented by the North American crayfish Procambarus clarkii (P. clarkii), an invasive species in Europe, mainly introduced for commercial purposes, causing a decline in biodiversity and profound habitat changes. The physical damages caused by P. clarkii on levees and banks, such as in rice fields, irrigation ditches, and small channels, have not been fully studied and behavioral components underlying this impact are mostly occasional. To understand the impact of burrowing activity on the seepage process, a field survey was done in a drainage channel in Tuscany, Italy, to evaluate the density and geometry of the internal burrows that were excavated by the crayfish. Based on these observations and some previous laboratory experiments, three dimensional (3D) numerical simulations of the seepage processes were done inside burrowed levees. Numerical results allowed the increase in the hydraulic vulnerability of levees to the process of internal seepage to be disclosed. In particular, for a given river water level, the reduction of the time scale for the phreatic line to reach the levee field side appears to be a function of a quantity here defined as the burrow hydraulic gradient. This quantity is here defined as the ratio between the hydraulic head inside the burrow and the horizontal distance from its end to the field side of the levee. Moreover, a comparison between the 3D with the analogous more common two dimensional (2D) numerical simulations illustrated the schematization which is better suited for describing the seepage processes when animal burrows, not only by crayfish, are present.